Caracterização do rejeito da separação magnética de rocha gnáissica na produção de areia de brita e avaliação de aplicações - Moura, Luanna Cavalcanti Rebecchi de (2019)
The characterization of waste originated in dry rare-earth magnetic separation used for processing of a gneiss rock for manufactured sand production included size, chemical and mineralogical analyses. In parallel, an assessment of two potential applications for this waste was carried out: slow release fertilizer and filler in polymers. The slow release fertilizer potential was simulated by extraction with the Mehlich-1 solution, to evaluate availability of free potash. The results show that the waste consisted predominantly of feldspar varieties, mica, quartz and amphibole group minerals. The material met all the requirements of Normative Instruction # 05 from 2016 for classification as slow release fertilizer, except for tests in the greenhouse, still pending. Availability of potassium by Mehlich-1 extraction after 480 h was 3.95 kg of K+ /t of magnetic waste powder (11.4% of total sample K + ). As filler in polymer, the study was performed by varying the particle size and amount of filler added to the polymer matrix. Regarding the particle size variation (5% added), results showed that the use of waste as received resulted in good absorption of electromagnetic waves, intermediate results for toughness, without impact on the isolated character, density or transition temperature of HDPE. Grinding this material (Poli02C-5) resulted in improvement in absorption performance (60% of absorption). Increased filler addition (20%), however, impaired polymer performance in all tests. Thus, the potential for applications of the mineral waste as slow release fertilizer and as functional extender in polymers with electromagnetic wave absorbing character, was demonstrated.